La dimensión ética en la elaboración del código de financiación responsable del FONPRODE: ¿ética o estética? Cambian las formas, ¿y el estado? - Carballo , Cecilia; Díaz, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
Leaving aside the debate over whether is necessary or not to involve the entire private sector in human development objectives pursued by financial cooperation, we believe that the FCR should have been based on the premise of whether what is good for the private sector is good for people in poverty, and have programmed in detail solutions (some of a penalty) to the possible negative externalities that may arise from doing business with the implementation of actions financed by the Fund.